Open Versus Arthroscopic Repair of 1B Ulnar-Sided Triangular Fibrocartilage Complex Tears: A Systematic Review. (July 2020) - Robba, Vanessa; Fowler, Andrew; Karantana, Alexia; Grindlay, Douglas; Lindau, Tommy
Background: Peripheral 1B tears of the triangular fibrocartilage complex (TFCC) can result in distal radioulnar joint (DRUJ) instability. In the context of associated DRUJ instability, combined evidence supports successful outcomes for peripheral tear repair.Methods: The aim of this systematic review (SR) was to compare the surgical treatment of 1B TFCC tears via arthroscopic versus open methods of repair. The primary outcome measure was restored DRUJ stability. The secondary outcome measures included patient-reported outcomes and clinical outcome measures. An electronic database search of Ovid Embase, PubMed, and the Cochrane Central Register of Controlled Trials was performed to cover a 20-year period. Two authors independently screened records for eligibility and extracted data.Results: Only 3 studies met the strict inclusion criteria, highlighting the poor evidence base for TFCC 1B repairs. Hence, a "secondary analysis" group was developed with modified inclusion criteria which included a further 7 studies for analysis. Pooled data from the primary and secondary analysis groups demonstrated that postoperative DRUJ stability was achieved following open repair in 84% (76/90) of cases and following arthroscopic repair in 86% (129/150) of cases.Conclusions: This SR demonstrates a current lack of high-quality evidence required to draw firm conclusions on the merits of arthroscopic versus open repair of 1B TFCC tears. There is no scientific evidence to suggest superiority of one technique over the other, albeit some surgeons and authors may express a strong personal view.